2009
DOI: 10.1103/physrevb.79.195407
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence sidebands of carbon nanotubes below the bright singlet excitonic levels

Abstract: We performed detailed photoluminescence ͑PL͒ spectroscopy studies of three different types of singlewalled carbon nanotubes ͑SWNTs͒ by using samples that contain essentially only one chiral type of SWNT, ͑6,5͒, ͑7,5͒, or ͑10,5͒. The observed PL spectra unambiguously show the existence of an emission sideband at ϳ140 meV below the lowest singlet excitonic ͑E 11 ͒ level, whose identity and origin are now under debate. We find that the energy separation between the E 11 level and the sideband is independent of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 41 publications
5
61
0
Order By: Relevance
“…symmetry phonons (henceforth referred to as Model #1) [14][15][16][17][18]. However, different models have been proposed by other studies, in which X2 was ascribed to be phonon sidebands of the B-Γ-S exciton coupled with zone-center Γ LO phonons, and X1 assigned to exciton peak of some dark deep excitonic state lying below the bright E 11 exciton (henceforth referred to as Model #2) [13,19].…”
mentioning
confidence: 99%
“…symmetry phonons (henceforth referred to as Model #1) [14][15][16][17][18]. However, different models have been proposed by other studies, in which X2 was ascribed to be phonon sidebands of the B-Γ-S exciton coupled with zone-center Γ LO phonons, and X1 assigned to exciton peak of some dark deep excitonic state lying below the bright E 11 exciton (henceforth referred to as Model #2) [13,19].…”
mentioning
confidence: 99%
“…In the case of the D-K-S exciton, phonon sidebands were believed to originate from the D-K-S exciton coupling with the zone-boundary A ′ 1 symmetry phonon [7,[19][20][21][22]. Energy of this D-K-S exciton (E K ) remains constant in magnetic fields within the available field range [13].…”
mentioning
confidence: 99%
“…Theoretical studies show that each sub-band manifold of SWNTs comprises a total of 16 excitonic states [12,13], among which the D-K-S and B-Γ-S excitons are two most probable candidates for the origin of phonon sidebands [6,7,[19][20][21][22][23]. In the case of the 1st sub-band transitions, there has been intense debate about the origin of the phonon sidebands, and it was confirmed recently that the D-K-S exciton is responsible for the observed phonon sidebands [7,8].…”
mentioning
confidence: 99%
“…In addition, there are two degenerate finite momentum states (K and K′-momentum excitons) with ∆E ≈ 36 meV for the (6,5) SWNT above the bright one. 23,24 Direct optical excitation of this state is forbidden, but it can be populated via a phonon sideband located at (∼E 11 + 200 meV ≈ E 11 1g + 170 meV). 23,25 Hertel et al found that after resonant E 22 excitation a large fraction of the E 22 excitons decay into this K momentum state.…”
mentioning
confidence: 99%